SAINS MENURUT SA‘ID AL-ANDALUSI MENERUSI KITAB TABAQAT AL-UMAM (Science According to Sa‘id Al-Andalusi through the Book of Tabaqat Al–Umam) - Mohd Ali, Mohd Zamrus Bin (Journal of Al-Tamaddun, 2019)
In the context of â€œscienceâ€ terminology, the expression of knowledge has led to the harmonization of building understanding of natural, human and The Creator. Through the philosophy and history of science, Muslim scholars consider this dimension as a characteristic synonymous with the phenomena of national civilization development, while the science functions that set the background to the natural phenomena dominate the pattern of national development. Said al-Andalusi discussed in Tabaqat al-Umam, the progress of national civilization development in the middle ages as a response to this issue. This study aims to survey the conceptual meaning of science from the perspective of science history. Also aims to identify the integrated and self-seeking development resulting from the multiple functions of science. Finally, to deepen understanding on the basic knowledge subjects in the context of science-based development. This research is based on literary study based on documentations, to gather data related to the questions under study and through data analysis that have been gathered for interpretation. The study found that the use of science terminology need to be properly understood without separating the original field of knowledge anchored on the concept of understanding the self, nature and The Creator. This also shows the correlation between the functions of science with the formation of national civilizations. This correlation will be a source of scientific exploration and give way to the advancement of science, able to strengthen the human rather than the symptoms of personal greed and ignorance about the philosophy of science.